Novel cruzipain inhibitors for the chemotherapy of chronic Chagas disease - Sbaraglini, Maria Laura (2016)
Despite current efforts worldwide to develop new medications against Chagas disease, only two drugs are available, nifurtimox and benznidazole. Both drugs require prolonged treatment and have multiple side effects and limited efficacy on adult patients chronically infected with Trypanosoma cruzi. Recently, computer-guided drug repositioning led to the discovery of the trypanocidal effects of clofazimine and benidipine. These compounds showed inhibitory effects on cruzipain, the major cysteine protease of T. cruzi, of different parasite stages and in a murine model of acute Chagas disease. The aim of this work was to determine the efficacy of these novel cruzipain inhibitors when administered in a murine model of chronic Chagas disease. Benidipine and clofazimine were able to reduce the parasite burden in cardiac and skeletal muscles of chronically infected mice compared with untreated mice as well as diminish the inflammatory process in these tissues. Further studies should be performed to study the synergism with benznidazole and nifurtimox in view of combined therapies.